Workshop Online: Prosedur Analisis Multidrug-Resistance Tuberculosis (MDR-TB) dengan Teknik Sekuensing Bagi Guru SD, SMP dan SMA - Koentjoro, Maharani Pertiwi; Bagas Dewantara Pratama Putra; Adyan Donastin; Endry Nugroho Prasetyo (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2021)
Teachers and students have difficulties in studying cell molecular in Cell Biology, Genetics, and Microbiology subjects. This difficulty is due to the molecular nature of the cell is something abstract and the learning media does not support the delivery of material. Therefore, in this community service activity, Laboratory Procedure Training in Analyzing Molecular Multidrug-Resistance Tuberculosis (MDR-TB) with Sequencing Techniques for Health Sector Teachers aims to provide teachers with understanding and skills regarding laboratory procedures in analyzing molecular MDR-TB with techniques sequencing. Activities are divided into 3 stages. Stage I is a pre-test to determine the teacher’s ability to analyze DNA. Phase II is the online training stage, which is divided into 3 meetings, where the first meeting is the delivery of DNA material, the second meeting is about laboratory procedures in DNA isolation, and the third meeting is bioinformatics techniques in DNA analysis. Stage III is a post-test, to find out whether the material and skills presented are acceptable to the participants or not. Based on the results of the evaluation through a questionnaire distributed to the participants at the end of the event, it can be concluded that around 76.1% of participants were satisfied with the workshop provided, as many as 50% were able to carry out the assignment to make poster teaching media, and 65.2% of participants were satisfied with the workshop method used.